Comparative Study of the Properties of High Voltage Spinel Cathode Material Depending on the Method of Synthesis - Kazda, Tómas (2014)
The most widely used cathode materials for lithium-ion accumulators nowadays are based on LiCoO2, LiFePO4 or LiMnO4. These materials are supposed to be replaced by battery systems with new generation of cathode materials such as sulphur-based or high-voltage cathode materials in the future. This article is focused on the study of electrochemical properties of high voltage cathode material LiCr0.1Ni0.4Mn1.5O4 depending on the process of synthesis. The samples were prepared by solid state reaction method with the temperature as an independent variable where electrochemical charge/discharge capacity retention was observed during cycling and also during cycling at different C rate. The structure and thermal stability of the particles of the synthesized materials was also studied by SEM and TGA.